Dialog Antaragama Berdasarkan Studi Alkitab Kisah Para Rasul 17:22-34 - Paisal, Paisal; Lusiana, Lusiana; Siregar, Esron Mangatas (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2024)
Maintaining harmony in a multicultural society is a must for believers through interfaith dialogue so that potential religious conflicts do not occur. So that interfaith tolerance can continue to be closely intertwined. Although it is certainly not easy to live together in a multi-tennis community environment because discrimination and exclusivity are still challenges in establishing effective dialogue. Through the book of Acts 17:22-34 are found Paul's ways of effectively dialogue with the philosophers in Athens as an approach to interfaith communication. With the aim of allowing everyone who has a different understanding to respect differences, and is not always oriented towards reaching an agreement. The author uses a qualitative method through a hermeneutic approach to texts and literature studies. The results of the analysis of interreligious dialogue based on the Bible study of Acts 17: 22-34 found that three approaches to dialogue are Dialogue about God: God is the Creator of the Universe, dialogue about the origin of human beings and about the last day to be a bridge and relevant to use.